Effect of hysterectomy on the risk of ovarian cancer: A South Korean national cohort study - Jin-Sung Yuk; Sang-Hee Yoon (PLoS ONE, 2026)
Background Hysterectomy is a common gynecological surgery, but its long-term impact on ovarian cancer risk remains unclear, particularly in Asian populations. Objective To evaluate the association between hysterectomy (with or without concomitant adnexal surgery) and the risk of ovarian cancer in South Korean women. Methods We conducted a retrospective cohort study using the Korean National Health Insurance Service (NHIS) database (2002–2020). After 1:1 propensity score matching, 13,059 women who underwent hysterectomy for benign indications (aged 40–59) were compared with 13,059 women without hysterectomy. The primary outcome was incident ovarian cancer, defined by three or more medical visits with a C56.xx diagnosis code. Cox proportional hazards models were used to estimate hazard ratios (HRs) for ovarian cancer, adjusting for demographic and clinical confounders. Results Over a median follow-up of 11.5 years, ovarian cancer incidence was 18 per 100,000 person-years in the hysterectomy group and 13 per 100,000 person-years in the non-hysterectomy group. Hysterectomy was associated with an imprecise estimate of ovarian cancer risk (HR 1.42, 95% CI 0.79–2.56), compatible with both a clinically meaningful decrease and increase in risk; therefore, the findings are inconclusive. There were no statistically significant differences between the two groups across various decades of life, including females below or above 50 years of age. Conclusions This study found no statistically significant association between hysterectomy and ovarian cancer risk, but the wide confidence intervals and limited number of events indicate that the findings remain inconclusive.